Method for choice of industrial hall walls variants optimization - Maciej Mielcarz; Paweł Nowak (Archives of Civil Engineering)
The current trends in the construction market require developing and completing building projects with balanced costs and the shortest execution time, while maintaining a high quality of works and properties of completed objects. Achieving this goal is difficult, however with the development of new technologies and management techniques, a sustainable project is possible to achieve. The authors’ goal was to find a technological solution which would efficiently meet the imposed requirements for optimizing the technology and organization project of the hall. Three technologies were analysed using the multi – criteria analysis based on the 6 aspects – all important from the sustainability point view. Choice and proper check of the criteria for sustainable decision making is crucial, as criteria are usually described by experts in not fully objective and mathematical way. Chosen elements of the Value Engineering (VE) practices were discussed and used. In order to evaluate each construction variant the weight of every criteria was determined using the Simos method and the variants’ data was normalized. The practicality of every construction variant as a sustainable solution was established through two evaluation methods – the entropy and the ideal point method. The results of this research prove that project managers can successfully achieve sustainable projects through the described optimization process. Similarly, this type of analysis can also be beneficial in other fields, such as mechanical engineering, finance, transportation, agriculture etc.